Dispositions of adults with low education levels, and who haven't returned to formal education, towards lifelong learning - Carvalho da Silva, V. (2021)
This study aims to determine how adults with low education levels perceive lifelong education by analyzing a set of interconnected and complementary aspects. The methodological strategy focussed on a qualitative analysis based on semi-directive interviews of a biographical nature. Identifying the reasons for the abandonment of initial (formal) education and obstacles faced by these adults over time revealed a myriad of factors justifying their disengagement from available education offers. To understand the amplitude of a phenomenon that links lifelong learning, knowledge, literacy and education level, in situations of a non-return to formal education, the study involved an in-depth analysis of the dispositions of persons who have “remained outside” of this relation with learning.